Analisa dan Pengembangan Sistem Informasi Penjualan BBM Berbasis Android - Rohmad Abidin; Taufik Kurnialensya (ECONBANK: Journal of Economics and Banking, 2021)
In managing reports on sales of fuel oil (BBM) at gas stations xxx Semarang using reports in the form of paper. The sales report paper is then recapitulated by the Administrative Officer. When going to perform data processing, the officer finds it difficult to present the sales data requested by the Manager. To overcome the problems that exist in the manual system, it is necessary to create a BBM Sales Information System so that data management and report generation can be done better. This research focuses on sales data for each type of fuel. To illustrate the requirements of the system using a use case diagram. The information system that will be created is built for the Android operating system that runs on tablet devices to make it easier for operators to fill in fuel sales data. The database used is SQLite because it is one of the databases that supports mobile devices. The new system development method uses a prototype model. The stages used in the development of this system include: the needs identification stage, the design design stage, the prototyping manufacturing stage, the testing stage and the implementation stage. The results of the development show that the Gas Station Sales Recording Application can run well because it is according to the manager needs